On relative widths of classes of differentiable functions. II - Subbotin, Yu. N.; Telyakovskii, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We obtain an upper bound for the least value of the factor $М$ for which the Kolmogorov widths $d_n (W_C^r, C)$ are equal to the relative widths $K_n (W^C_r, MW^C_j, C)$ of the class of functions $W_C^r$ with respect to the class $MW^C_j$, provided that $j > r$. This estimate is also true in the case where the space $L$ is considered instead of $C$.